Membrane electrode with porous structure and gradient hydrophilic catalyst layer and preparation method thereof
By adopting a porous structure and gradient hydrophilic design in the anode catalytic layer of the membrane electrode, the problem of difficulty in mass transfer under large current density is solved, and the electrochemical performance is significantly improved.
Patent Information
- Application Number
- CN202411970522.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-18
AI Technical Summary
The traditional anode catalytic layer structure is disordered and dense, and has low porosity, which makes it difficult for the electrolytic cell to transfer mass under high current density, which in turn leads to a reduced electrochemical performance.
A membrane electrode with a porous structure and a gradient hydrophilic catalytic layer is adopted. The anode catalytic layer is composed of two sub-catalytic layers. The inner layer contains SiO2 nanoparticles and the outer layer contains MgO nanoparticles. MgO is removed by dilute sulfuric acid treatment to form a porous structure.
The porosity and pore size of the catalytic layer are improved, the vapor-liquid transmission is enhanced, the three-phase interface of the catalytic layer is increased, and the electrochemical performance is improved, especially the mass transfer performance under high current density.
Smart Images

Figure CN119843304A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water, and relates to a membrane electrode with a porous structure and a gradient hydrophilic catalytic layer and a preparation method thereof. Background Art
[0002] Hydrogen energy is considered to be a promising green energy source due to its high energy density, clean and pollution-free, and wide range of applications. It is expected to become a new secondary energy source. Proton exchange membrane water electrolysis uses solid electrolytes to produce hydrogen, which has improved ohmic conductivity and mechanical strength. It has higher current density, more compact structural design and wider working range, and is a promising hydrogen production method. The membrane electrode is a key component of the proton exchange membrane water electrolyzer. The anode catalyst layer in the membrane electrode determines the performance and efficiency of the proton exchange membrane water electrolyzer: the O2 produced by the anode reaction must be discharged as soon as possible to ensure the continuous electrochemical reaction. Otherwise, the accumulation of O2 in the catalyst layer will block the supply of reactants and cause the membrane to dry out, reducing the life of the proton exchange membrane water electrolyzer.
[0003] However, the conventional anode catalyst layer has a disordered and dense structure and low porosity, which makes it difficult to transfer mass in the electrolytic cell at high current density. Currently, few studies have focused on the mass transfer phenomenon of electrolytic cells at high current density and the resulting reduction in electrochemical performance. Summary of the invention
[0004] The technical solution adopted by the present invention to solve the technical problem is: a membrane electrode having a porous structure and a gradient hydrophilic catalyst layer, wherein the anode catalyst layer of the membrane electrode comprises two sub-catalytic layers; the two sub-catalytic layers are sequentially divided into an inner layer and an outer layer from the proton exchange membrane side to the anode diffusion layer side;
[0005] The anode catalyst layer contains 30-40 vol% MgO nanoparticles, and the particle size of the nanoparticles is 50-80 nm;
[0006] The inner layer contains 3-10 wt% SiO2 nanoparticles, and the outer layer contains no SiO2.
[0007] Preferably, the anode catalyst layer contains 35-37 vol% MgO nanoparticles; and the inner layer contains 4.5-5.5 wt% SiO2 nanoparticles.
[0008] Preferably, the anode catalyst of the membrane electrode is IrO2, and the cathode catalyst of the membrane electrode is Pt / C.
[0009] The present invention also discloses a method for preparing a membrane electrode having a porous structure and a gradient hydrophilic catalytic layer. The method is used to prepare the membrane electrode having a porous structure and a gradient hydrophilic catalytic layer. The method comprises the following steps:
[0010] Step I: mixing the cathode catalyst with deionized water, and then adding a certain amount of isopropanol; adding an ionomer to the mixed solution, and ultrasonically treating it in ice water to prepare a cathode catalyst slurry;
[0011] Step II. Mixing the anode catalyst with deionized water, and then adding a certain amount of isopropanol; adding the ionomer to the mixed solution, and ultrasonically treating it in ice water; then adding SiO2 or MgO, and continuing the ultrasonic treatment to prepare the anode catalyst slurry;
[0012] Step III. Spray the cathode catalyst slurry on one side of the proton exchange membrane by direct spraying; spray the anode catalyst layer slurry on the other side of the proton exchange membrane: the slurry used for spraying the inner layer of the anode catalyst layer contains SiO2 and MgO; the slurry used for spraying the outer layer of the anode catalyst layer contains MgO;
[0013] Step IV. Treat the membrane electrode obtained in step III in dilute sulfuric acid, then rinse with deionized water and dry; the anode catalyst layer of the treated membrane electrode is an inner hydrophilic porous structure catalyst layer; The effect of treating the membrane electrode obtained in step III in dilute sulfuric acid is to remove MgO in the catalyst layer, which is very effective for the formation of a porous structure.
[0014] Preferably, during the ultrasonic treatment in ice water in step I, the temperature of the ice water is 11-20° C.; ice water is beneficial to the dispersion of the anode catalyst IrO2, preventing the agglomeration of catalyst particles, and has a significant effect on improving the overall performance.
[0015] Preferably, when deionized water and isopropanol are mixed in step I and step II, the mixing volume ratio of deionized water to isopropanol is 1:1 to 1:4; the mixing volume ratio of deionized water to isopropanol is beneficial to the dispersion of the anode catalyst IrO2, prevents the agglomeration of the catalyst particles, and has a significant effect on improving the overall performance.
[0016] Preferably, the ionomer in step I and step II is Nafion D520.
[0017] The beneficial effects of the present invention are:
[0018] 1. The anode catalyst layer of the porous structure catalyst layer in the present invention comprises two sub-catalyst layers, which are an inner layer and an outer layer, respectively, from the proton exchange membrane to the anode diffusion layer side; the hydrophilicity in the catalyst layer decreases from the membrane side to the diffusion layer side, and the constructed hydrophilicity gradient is conducive to driving the bubbles to move to the diffusion layer side, thereby realizing the rapid transfer of products; after adding SiO2 into the catalyst layer, its surface contact angle decreases, indicating that its hydrophilicity is enhanced; therefore, the present invention solves the mass transfer difficulty problem of the anode catalyst layer of the proton exchange membrane electrolyzer in the prior art.
[0019] 2. The porous structure of the present invention improves the porosity of the catalyst layer and increases the pore size, which is beneficial to the gas-liquid transmission in the catalyst layer; the pore-forming agent MgO can increase the three-phase interface of the catalyst layer, and the kinetic activity of the catalyst layer is enhanced; the inner hydrophilic porous structure catalyst layer therefore has good electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram comparing a common catalytic layer and an inner hydrophilic porous catalytic layer of a membrane electrode having a porous structure and a gradient hydrophilic catalytic layer and a preparation method thereof of the present invention;
[0021] Figure 2 It is a schematic diagram comparing the surface contact angles of a common catalyst layer and a catalyst layer containing 5 wt% SiO2 of the present invention;
[0022] Figure 3 It is a schematic diagram comparing the surface morphologies of a common catalyst layer and a catalyst layer containing 36 vol% MgO of the present invention;
[0023] Figure 4 It is a schematic diagram comparing the electrochemical performances of membrane electrodes prepared with four different structures of anode catalyst layers of the present invention, which are assembled into electrolytic cells for testing. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] This embodiment aims to provide a simple and easy-to-operate membrane electrode and its preparation method and application, and improve the electrochemical performance and efficiency of the proton exchange membrane water electrolysis cell by regulating the hydrophilicity gradient and porous structure of the catalytic layer.
[0026] Technical Solution
[0027] The present embodiment is applied to the membrane electrode of the proton exchange membrane water electrolyzer, including a proton exchange membrane and an anode catalyst layer and a cathode catalyst layer respectively deposited on both sides thereof, wherein the anode catalyst layer is a porous catalyst layer with a hydrophilic inner layer.
[0028] In this embodiment, the anode catalyst layer includes two sub-catalytic layers. From the proton exchange membrane to the anode diffusion layer side, there are inner and outer layers, and the catalyst loading of each layer is the same. The anode catalyst layer contains 36 vol% MgO nanoparticles with a particle size of 50 to 80 nm. The inner layer contains 5 wt% SiO2 nanoparticles, and the outer layer has no SiO2.
[0029] In this embodiment, the anode catalyst used is IrO2; the cathode catalyst used is Pt / C.
[0030] Preparation method
[0031] I. The cathode catalyst is mixed with deionized water, and then a certain amount of isopropanol is added. The ionomer is added to the mixed solution, and ultrasonic treatment is performed in ice water to prepare a cathode catalyst slurry.
[0032] II. The anode catalyst is mixed with deionized water, and then a certain amount of isopropanol is added. The ionomer is added to the mixed solution, and ultrasonic treatment is performed in ice water. SiO2 or MgO is then added, and ultrasonic treatment is continued to prepare the anode catalyst slurry.
[0033] III. By direct spraying, the cathode catalyst slurry is sprayed on one side of the proton exchange membrane; the anode catalyst layer slurry is sprayed on the other side of the proton exchange membrane: the slurry used for spraying the inner layer of the anode catalyst layer contains SiO2 and MgO; the slurry used for spraying the outer layer of the anode catalyst layer contains MgO.
[0034] IV. The membrane electrode obtained in step III is treated in dilute sulfuric acid, and then washed with deionized water and dried. The anode catalyst layer of the treated membrane electrode is an inner hydrophilic porous catalyst layer.
[0035] Wherein, in step I, the ultrasonic treatment is carried out in ice water, and the temperature of the ice water is 11-20°C.
[0036] Wherein, the deionized water and isopropanol described in step I and step II are mixed in a mixing volume ratio of 1:1 to 1:4.
[0037] Example
[0038] refer to Figures 1 to 4 The specific implementation scheme of this embodiment is shown in Table 1 below:
[0039] name <![CDATA[SiO2]]> MgO <![CDATA[Anode (mg Ir ·cm -2 )]]> <![CDATA[cathode (mg Pt ·cm -2 )]]> Non-Optimizing none none 0.45 0.25 inner Inner layer 5wt% none 0.45 0.25 PoreFormer none 36vol% 0.45 0.25 inner+PF Inner layer 5wt% 36vol% 0.45 0.25
[0040] Table 1
[0041] The cathode catalyst layer slurry configurations of the above four membrane electrodes are the same, as follows:
[0042] 6 mg of 40% Pt / C was mixed with 1.2 ml of water, and 1.2 ml of isopropanol was added. 36 μl of Nafion D520 was added, and the mixture was sonicated in ice water for 1 h.
[0043] For anode catalyst slurry:
[0044] Non-Optimizing (ordinary catalytic layer):
[0045] Mix 6 mg IrO2 with 0.5 ml water, add 1.4 ml isopropanol, add 15 μl Nafion D520, and sonicate in ice water for 1 h.
[0046] Inner (inner hydrophilic catalytic layer):
[0047] Slurry 1: Mix 6 mg IrO2 with 0.5 ml water, add 1.4 ml isopropanol, add 15 μl Nafion D520, and sonicate in ice water for 1 h.
[0048] Slurry 2: Mix 38 mg IrO2 with 3.2 ml water and add 8.9 ml isopropanol. Add 95
[0049] μl Nafion D520. Ultrasonic treatment in ice water for 30 min. Add 2 mg SiO2.
[0050] When preparing this membrane electrode, slurry 1 is first used for spraying. After the IrO2 reaches half of the specified loading amount, slurry 2 is used for spraying until the IrO2 loading amount is the same as the other three cases.
[0051] PoreFormer (porous structure catalytic layer):
[0052] Mix 12 mg IrO2 with 1 ml water, add 2.8 ml isopropanol, add 30 μl Nafion D520, sonicate in ice water for 30 min, and add 2 mg MgO (particle size 50-80 nm).
[0053] Inner+PF (inner hydrophilic porous catalytic layer):
[0054] Slurry 1: Mix 38 mg IrO2 with 3.2 ml water, add 8.9 ml isopropanol, add 95 μl Nafion D520, sonicate in ice water for 30 min, add 2 mg SiO2, 6.3 mg MgO.
[0055] Slurry 2: Mix 12 mg IrO2 with 1 ml water, add 2.8 ml isopropanol, add 30 μl Nafion D520, sonicate in ice water for 30 min, add 2 mg MgO (particle size 50-80 nm).
[0056] This membrane electrode was prepared in the same manner as inner. Slurry 1 was first sprayed, and after IrO2 reached half of the specified loading, slurry 2 was sprayed until the IrO2 loading was the same as the other three cases.
[0057] The preparation methods of the cathode and anode catalyst layers corresponding to the four membrane electrodes are as above. For all membrane electrodes: the cathode catalyst loading is 0.25 mg Pt cm -2 , the anode catalyst loading is 0.45 mg Ir cm -2 .
[0058] Figure 1 Schematic diagram of a common catalyst layer and a hydrophilic inner layer with a porous structure. Figure 1 (a) is a common catalytic layer; Figure 1 (b) is a hydrophilic inner porous catalytic layer;
[0059] Figure 2 The surface contact angles of the ordinary catalyst layer and the catalyst layer containing 5wt% SiO2. After adding SiO2 to the catalyst layer, its surface contact angle decreases, indicating that its hydrophilicity is enhanced. Figure 2 (a) is a common catalytic layer; Figure 2 (b) is a catalyst layer containing 5wt% SiO2;
[0060] Figure 3 The surface morphology of the ordinary catalyst layer and the catalyst layer containing 36 vol% MgO. After adding MgO to the catalyst layer and removing it with dilute sulfuric acid, the catalyst layer becomes more porous. Figure 3 (a) is a common catalytic layer; Figure 3 (b) is a catalyst layer containing 36 vol% MgO;
[0061] Figure 4 The electrochemical performance of membrane electrodes prepared for four different structures of anode catalyst layers was tested in electrolytic cells. Figure 4 (a) is the polarization curve at 6A·cm -2 Under the condition of Non-Optimizing, inner, PoreFormer, inner+PF, the voltages are 2.238V, 2.201V, 2.184V, and 2.164V. The inner layer hydrophilicity adjustment or porous structure can improve the mass transfer performance of MEA. The porous structure catalyst layer with inner hydrophilicity prepared by combining the two structures can further improve the performance of MEA under high current density. -2 Compared with Non-Optimizing, the overpotential of inner+PF is reduced by 74mV. Figure 4 (b) is the electrochemical impedance spectrum at 1.5 V. The charge transfer resistance of Non-Optimizing, inner, PoreFormer, and inner+PF are 308.21 mΩ·cm, respectively. 2 、359.04mΩ·cm 2、279.23mΩ·cm 2 、291.31mΩ·cm 2 The pore-forming agent MgO can increase the three-phase interface of the catalyst layer and enhance the kinetic activity of the catalyst layer; the addition of SiO2 to the inner layer of the catalyst layer leads to a slight decrease in the kinetic performance of the catalyst layer, which is due to the covering of some active sites by SiO2; the charge transfer resistance of inner+PF is the result of the combined effect of the pore-forming agent MgO and SiO2.
[0062] In summary, the hydrophilicity of the catalyst layer of the present invention decreases from the membrane side to the diffusion layer side, and the constructed hydrophilicity gradient is beneficial to driving the bubbles to move to the diffusion layer side, thereby realizing the rapid transfer of products; after adding SiO2 in the catalyst layer, its surface contact angle decreases, indicating that its hydrophilicity is enhanced; therefore, the present invention solves the problem of mass transfer difficulties in the anode catalyst layer of the proton exchange membrane electrolyzer in the prior art.
[0063] It should be emphasized that the above are only preferred embodiments of the present invention and do not limit the present invention in any form. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A membrane electrode having a porous structure and a gradient hydrophilic catalyst layer, characterized in that: The anode catalyst layer of the membrane electrode comprises two sub-catalytic layers; the two sub-catalytic layers are divided into an inner layer and an outer layer from the proton exchange membrane side to the anode diffusion layer side; The anode catalyst layer contains 30-40 vol% MgO nanoparticles, and the particle size of the nanoparticles is 50-80 nm; The inner layer contains 3-10 wt% SiO2 nanoparticles, and the outer layer contains no SiO2.
2. The membrane electrode having a porous structure and a gradient hydrophilic catalyst layer according to claim 1, characterized in that: The anode catalyst layer contains 35-37 vol% MgO nanoparticles; the inner layer contains 4.5-5.5 wt% SiO2 nanoparticles.
3. The membrane electrode having a porous structure and a gradient hydrophilic catalyst layer according to claim 1, characterized in that: The anode catalyst of the membrane electrode is IrO2, and the cathode catalyst of the membrane electrode is Pt / C.
4. A method for preparing a membrane electrode having a porous structure and a gradient hydrophilic catalyst layer, characterized in that: The preparation method is used to prepare the membrane electrode having a porous structure and a gradient hydrophilic catalytic layer according to any one of claims 1 to 3, and the preparation method comprises the following steps: Step I: mixing the cathode catalyst with deionized water, and then adding isopropanol; adding ionomer to the mixed solution, and ultrasonically treating in ice water to prepare a cathode catalyst slurry; Step II. Mixing the anode catalyst with deionized water, and then adding isopropanol; adding the ionomer to the mixed solution, and ultrasonically treating it in ice water; then adding SiO2 or MgO, and continuing the ultrasonic treatment to prepare the anode catalyst slurry; Step III. Spray the cathode catalyst slurry on one side of the proton exchange membrane by direct spraying; spray the anode catalyst layer slurry on the other side of the proton exchange membrane: the slurry used for spraying the inner layer of the anode catalyst layer contains SiO2 and MgO; the slurry used for spraying the outer layer of the anode catalyst layer contains MgO; Step IV. The membrane electrode obtained in step III is placed in dilute sulfuric acid for treatment, and then washed with deionized water and dried; the anode catalyst layer of the treated membrane electrode is an inner hydrophilic porous catalyst layer.
5. The method for preparing a membrane electrode having a porous structure and a gradient hydrophilic catalyst layer according to claim 4, characterized in that: When the ultrasonic treatment is performed in ice water in step I, the temperature of the ice water is 11-20°C.
6. The method for preparing a membrane electrode having a porous structure and a gradient hydrophilic catalyst layer according to claim 4, characterized in that: When deionized water and isopropanol are mixed in step I and step II, the mixing volume ratio of the deionized water and isopropanol is 1:1 to 1:
4.
7. The method for preparing a membrane electrode having a porous structure and a gradient hydrophilic catalyst layer according to claim 4, characterized in that: The ionomer in step I and step II is: Nafion D520.
Citation Information
Patent Citations
Hydrophilic / hydrophobic compound multilayer membrane electrode and preparation method thereof
CN106229533A
A membrane-electrode three-in-one assembly with a composite catalytic layer and its preparation method
CN106961838B
Membrane electrode with adjustable pore structure and preparation method of membrane electrode
CN109713321A
Anode catalyst layer with high reversal tolerance, preparation of anode catalyst layer and application of anode catalyst layer to membrane electrode and fuel cell
CN113851658A
Electrolytic cell membrane electrode with controllable and adjustable pore structure as well as preparation method and application of electrolytic cell membrane electrode
CN115011986A